Statistical analysis of effective variable parameters on corrosion rate of X52 carbons steel - Zahidah, K.A. (Asian Research Publishing Network, 2016)
Nowadays, carbon and low alloy steels are widely exercised in pipeline construction. By having high pressure of CO2 which is used for the flooding reservoir, the oil fields lifetime could be increase. Basically, CO2 are able to dissolve in the existence of the brine water and forming carbonic acid. Carbonic acid could be expressed as a corrosive media. Inhibitor injection method can be used to prevent CO2 corrosion in the pipeline. Imidazoline is one of the most common corrosion inhibitor which is used to prevent CO2 corrosion. This inhibitor has high effectiveness towards corrosion mitigation. The corrosion rate is related to various factors such as; temperature, inhibitor concentration, and pH of environment. In this study, corrosion rate measurements were done based on weight loss test and linear polarization resistance (LPR) test, the results proved that the corrosion rate will become lower at greater inhibitor concentration. Furthermore, the corrosion rate will greatly increase due to decreasing in pH of the surrounding. Moreover, the corrosion rate will slightly increase as the temperature of the surrounding increase. As an overall conclusion, this research would benefit one to estimate the corrosion rate in different surrounding condition by inserting the values of factor A, B, and C in this provided governing equation harvested by Box Behnken design. Â© 2006-2016 Asian Research Publishing Network (ARPN).